2017
DOI: 10.5530/jyp.2017.9.84
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and Dissolution Enhancement of Meropenem by Nano Suspension Approach

Abstract: Objective: To prepare and evaluate the suitable nanosuspensions of Meropenem (BCS-IV drug) to increase its solubility and dissolution. Methodology: The meropenem nanosuspensions were prepared by emulsification solvent evaporation technique by applying ultrasonic energy through probe sonicator, where the organic phase of drug solution in methanol was emulsified in aqueous phase containing hydroxy propyl methyl cellulose as solubilizer and sodium lauryl sulphate as stabilizer. The prepared nanosuspensions were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Small pores appeared in the structure due to the F127, which supported the diffusion of water molecules around the structure. This also showed the greater influence of the polymers in the network structure and explained the greater interaction of the polymers within the hydrogel [60]. The expanded structure achieved a more stable and diffusible hydrogel, and the porous network could hold more water, facilitating the swelling of the hydrogel; similarly, the tiny pores on the surface suggested that the drug release from the hydrogel would occur in a sustainable manner [61].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 84%
“…Small pores appeared in the structure due to the F127, which supported the diffusion of water molecules around the structure. This also showed the greater influence of the polymers in the network structure and explained the greater interaction of the polymers within the hydrogel [60]. The expanded structure achieved a more stable and diffusible hydrogel, and the porous network could hold more water, facilitating the swelling of the hydrogel; similarly, the tiny pores on the surface suggested that the drug release from the hydrogel would occur in a sustainable manner [61].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 84%